Pedagogy of the Memory and Performative Writing in Human Rights Education - Cubillos Vega, Carla (2018)
One of the main challenges facing human rights education is to constitute an ethical-politicaleducation that, in addition to making them known, pursues the emancipation of people, promotingpositive attitudes about their values and fostering their critical reflection. The aim ofthis work, framed in critical pedagogies, is to explore the pedagogy of memory and performativeresearch in human rights education. Thus, we exemplify an experience designed around thispedagogical framework, developed in the field of higher education; participants were studentsfrom a teacher training course of a Higher Institute of the city of Rosario, Argentina. Theexperience was collected through direct observation and has been analyzed in light of thetheoretical framework outlined. The engagement with the values of human rights requires asignificant learning; in that sense, we noted that participants could explore “otherness”, reflecton the human dignity and experience the ethical dilemmas that arise when particular desiresand interests conflict in social interaction. We conclude that dramatic writing as performativepractice has great potential in allowing the exploration of emotions and mobilizing them towardsan understanding of the conflicts that arise from human interrelationships and, withina framework of pedagogy of memory, this allows us to recover, interpret and resignify history.